Trends and characteristics of multidrug-resistant MRSA in Norway 2008-2020 - Rønning, Torunn Gresdal; Enger, Hege; Afset, Jan Egil; Ås, Christina Gabrielsen (Frontiers in Microbiology, 2025)
Infections caused by multidrug-resistant (MDR) bacteria are recognized as a critical One Health concern which poses a significant threat to public health, leading to increased morbidity and mortality across both high- and low-income countries. In this study, we investigated the epidemiology and molecular mechanisms of multidrug-resistant methicillin-resistant Staphylococcus aureus (MDR-MRSA) strains identified in Norway from 2008 to 2020, in order to gain a better understanding of the evolution and dissemination of multidrug resistance in S. aureus. A total of 452 MDR-MRSA strains isolated from 429 individuals were analyzed from a dataset of 23,412 MRSA strains. Methods included epidemiological characterization, antimicrobial susceptibility testing (AST), and genetic analysis of a selection of strains using nanopore sequencing to identify antimicrobial resistance (AMR) genes and mutations, as well as their location on plasmids, SCCmec and other mobile genetic elements (MGEs). The study revealed an overall increasing trend in MDR-MRSA strains, with healthcare-associated strains being more prevalent among MDR-MRSA compared to the overall MRSA population. Significant heterogeneity in spa-types and clonal complexes exhibiting multidrug resistance was observed, with high resistance rates against multiple antibiotic groups, particularly erythromycin, ciprofloxacin/norfloxacin, tetracycline, gentamicin, and clindamycin in addition to cefoxitin. The predominant MDR-MRSA clones included t1476/CC8, t127/CC1, t189/CC188, and t030, t037/CC239. Among these, MRSA t1476/CC8 showed an upward trend toward the conclusion of the study period, indicating the emergence of a MDR-MRSA clone. A broad range of AMR genes and mutations were detected, linked to a wide variety of MGEs, highlighting the complex mechanisms of resistance development and dissemination within the MRSA population. This study highlights the rising challenge posed by MDR-MRSA strains, and reveals the multifactorial nature of AMR in S. aureus, thus emphasizing the importance of continued surveillance, antibiotic stewardship and infection control measures, as well as global cooperation, in order to combat the spread of these multidrug-resistant pathogens.